THE ROLE OF TEACHER EDUCATION IN ENHANCING EDUCATIONAL QUALITY - Sekar Purbarini Kawuryan (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2023)
Teacher education plays a fundamental role in shaping the quality and effectiveness of education systems worldwide. This paper explores how structured and continuous teacher preparation contributes to improved teaching practices, student outcomes, and educational equity. Through a qualitative, literature-based approach, the study examines key elements of successful teacher education programs, including the integration of theory and practice, ongoing professional development, and the role of teacher educators. The findings suggest that countries investing in robust teacher education systems consistently achieve higher educational performance. However, challenges remain, including the theory-practice gap, insufficient training in digital pedagogy, and inequities in access to quality programs. Addressing these challenges requires coordinated policy reform and sustained investment. Ultimately, enhancing teacher education is essential for building inclusive, adaptive, and high-performing education systems capable of meeting 21st-century demands.